1989
DOI: 10.1177/004728758902700306
|View full text |Cite
|
Sign up to set email alerts
|

A Model Of Tourists' Propensity To Buy: The Case Of Japanese Visitors To Hawaii

Abstract: The findings of a survey of 490 Japanese tourists visiting Hawaii suggest a model for tourists' propensity to buy goods in a vacation destination. The verbal model considers types of products available, level of domestic tax and import duties, relative value of specific goods, and retailer strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
3

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 2 publications
2
63
0
3
Order By: Relevance
“…According to Keown (1989), relative prices are one of the most influential factors in shopping tourism. He hypothesized that the cheaper the prices in a des-tination, the more popular the destination would be for shopping.…”
Section: Motivation To Shop In Shopping Tourismmentioning
confidence: 99%
“…According to Keown (1989), relative prices are one of the most influential factors in shopping tourism. He hypothesized that the cheaper the prices in a des-tination, the more popular the destination would be for shopping.…”
Section: Motivation To Shop In Shopping Tourismmentioning
confidence: 99%
“…In travel, tourists do shopping as one of the habits/ activities. For most tourists, in fact, a vacation experience would become in complete without opportunities to shop (Keown 1989;Reisinger, Turner 2001). Most tourists do shopping and buy souvenirs, artworks, etc.…”
Section: Craft Village Tourism (Craft Tourism) and Its Roles In Vietnmentioning
confidence: 99%
“…Keown [34] found that approximately 80% of Japanese visitors to Hawaii spent more than five hours on shopping. Approximately 30% of their spending was allocated to themselves and 60% to family, friends and work associates.…”
Section: Review Of Literaturementioning
confidence: 99%